2021
DOI: 10.3390/ijerph18020762
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Transport in the Coastal Unconfined Aquifer under the Influences of Seawater Intrusion and Inland Freshwater Recharge—Laboratory Experiments and Numerical Simulations

Abstract: The coupled effect of seawater intrusion and inland freshwater recharge plays an important role in contamination transport in coastal heterogeneous aquifer. In this study, the effects of seawater intrusion and inland recharge on contamination transport were investigated by conducting laboratory experiments and numerical simulations. The laboratory tests were conducted in a sand tank considering two scenarios, namely the conditions of landward and seaward hydraulic gradients. The SEAWAT software was applied for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This could be attributed to the dilution of the concentration of contaminants as the water flows downward 110,111 . This indicated that the contaminants in the studied water channel were diluted by the flow of the river 112,113 .…”
Section: Resultsmentioning
confidence: 91%
“…This could be attributed to the dilution of the concentration of contaminants as the water flows downward 110,111 . This indicated that the contaminants in the studied water channel were diluted by the flow of the river 112,113 .…”
Section: Resultsmentioning
confidence: 91%
“…This discretization is often achieved through finite difference or finite element methods, and the process is iteratively repeated at each time step. These numerical models are extensively employed in aquifer resource management (Omar et al 2020;Miro et al 2021;Ostad-Ali-Askari & Shayannejad 2021), design of aquifer storage and recovery schemes (LaHaye et al 2021;Tiwari et al 2022Tiwari et al , 2023, drought risk management (Shivakoti et al 2019;Wossenyeleh et al 2021), and aquifer pollution control (Robinson et al 2009;Guo et al 2021;Panjehfouladgaran & Rajabi 2022;Shakeri et al 2023). However, the computational expense of numerical methods used in regional groundwater simulations can pose a significant obstacle for tasks that involve repeated simulations, such as uncertainty analysis and simulation-based optimization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, coastal aquifers are subject to the inflow of seawater, which represents the main limitation for groundwater uses [ 16 , 17 ]. Saltwater intrusion can be considered a very serious hazard to coastal areas that threatens fresh water supplies needed for livelihood [ 18 ].…”
Section: Introductionmentioning
confidence: 99%